Describing Chinese Herbal Medicine Telehealth Care for Symptoms Related to Infectious Diseases Such as COVID-19: A Prospective, Longitudinal, Descriptive Cohort Study Protocol - Lisa Taylor-Swanson; Bob Wong; Belinda J. Anderson; Lee Hullender Rubin; Iman Majd; Daniel Altschuler; Daniel Bensky; Shouchun Ma; Craig Mitchell; Katherine Taromina; Misha Cohen; Lisa Conboy (Mary Ann Liebert, 2024)
Aim: The aim of our study is to describe Chinese herbal medicine (CHM) therapy, outcomes, and safety with patients experiencing symptoms possibly related to the novel 2019 Coronavirus (COVID-19). Method: In this ongoing prospective, longitudinal, descriptive cohort study at an East Asian medicine school clinical faculty practice, we are observing participants with symptoms related to COVID-19 who consent to participate in telehealth visits and receive individualized CHM. Following screening according to inclusion and exclusion criteria, all participants are asked to obtain a COVID-19 test at the time of enrollment. Licensed practitioners with at least 15 years of CHM practice experience are determining the number of telehealth consultations necessary for each participant. All participants are recommended individualized CHM dispensed either as loose herbs to be decocted at home or granules. Follow-up at 24 and 48?h after each telehealth consult will provide clinicians with information to determine if an additional telehealth consultation is necessary. Additional scheduled follow-up is at 3, 6, and 12 months. We began this study observing telehealth interactions as the clinic was closed to in-person visits. The clinic opened again to in-person visits in late 2020, and we have continued data collection. Ethics and Dissemination: The study has received Institutional Review Board ethics approval and is currently enrolling. Data from this cohort study will be presented online for real-time dissemination to clinicians and scientists, at scientific conferences, and published in peer-review journals. Describing individualized CHM treatment as a potential COVID-19 therapy will provide vital preliminary data on methods, feasibility, acceptability, tolerability, effectiveness, and safety. Findings from our study will inform future controlled trials of individualized CHM therapy for symptoms related to COVID-19. Trial Registration: ClinicalTrials.gov registration number: NCT04380870.